The Hitchin fibration under degenerations to noded Riemann surfaces - Swoboda, Jan (Abhandlungen aus dem Mathematischen Seminar der Universität Hamburg, 2016)
In this note we study some analytic properties of the linearized self-duality equations on a family of smooth Riemann surfaces $$Σ _R$$ΣRconverging for $$R\searrow 0$$R↘0to a surface $$Σ _0$$Σ0with a finite number of nodes. It is shown that the linearization along the fibres of the Hitchin fibration $$\mathcal M_d→ Σ _R$$Md→ΣRgives rise to a graph-continuous Fredholm family, the index of it being stable when passing to the limit. We also report on similarities and differences between properties of the Hitchin fibration in this degeneration and in the limit of large Higgs fields as studied in Mazzeo et al. (Duke Math. J. 165(12):2227-2271, 2016).